The health and security of women and girls following disaster: A qualitative investigation in post-earthquake Nepal. (December 2021) - Tearne, Jessica E.; Guragain, Bhushan; Ghimire, Lajina; Leaning, Jennifer; Newnham, Elizabeth A.
Abstract: Background: Nepal's April 2015 earthquakes were among the largest and deadliest in the country's history, affecting eight million people. Globally, women and girls are disproportionately exposed to risk during and in the aftermath of disaster. This study sought to examine the unique security and health risks for women and girls in post-earthquake Nepal. Method: Thirty-five adolescents (ages 13–19; 48.6% female) and 27 adults (ages 23–58; 55.6% female) from three disaster-affected areas of Nepal (Bhaktapur, Kathmandu, and Lalitpur) took part in the study in January and February of 2016. Data were collected through twenty semi-structured key informant interviews and five focus group discussions, recorded in Nepali and translated into English for analysis. Data were analysed using Thematic Content Analysis. Results: Multiple health and security risks for women and girls emerged following the earthquakes. A key theme was the risk of violence (including domestic and sexual violence) and trafficking in this population. Concerns were also raised regarding physical health and sanitation risks unique to girls and women, including a lack of appropriate resources and private facilities. Finally, the disproportionate impact of disaster on women's livelihoods emerged as a significant theme in the data. Conclusions: Despite great progress toward gender equity in Nepal in recent decades, pre-existing risk factors and embedded gender beliefs intersected with novel disaster-induced stressors to produce a range of health and security risks for women and girls. Incorporation of existing frameworks for gender-mainstreaming in disaster preparedness and response efforts is thus crucial to improve inclusivity in risk reduction.